Optimal Pricing Decisions for Dual-Channel Supply Chain: Blockchain Adoption and Consumer Sensitivity - Rong Zhang; Zhiwei Xia; Bin Liu (Complexity)
Counterfeiting is common in many industries. For the authenticity of online channel products and to combat counterfeiting, many companies have begun to use blockchain technology to trace product information. This paper investigates a dual-channel supply chain consisting of one manufacturer and one retailer, in which the manufacturer sells its standard products through the retailer and adopts blockchain technology to launch the online channel to sell the traceable products. A Stackelberg game is developed to depict the pricing decision and channel strategy choice for the manufacturer. It shows that both the manufacturer and the retailer can benefit from blockchain adoption. And the longer it takes for product traceability, the lower the price of online traceable products. It is beneficial for the manufacturer when consumers in the market are less concerned about information transparency. For consumer sensitivity, as consumers’ acceptance of direct sales channels increases, the selling prices of online traceable products have risen. Furthermore, as the traceability time-sensitivity coefficient increases, the sales price of the traceable products decreases, and the retail price of offline standard products rises. The conclusion of this paper has a certain guiding role for the dominant manufacturers in choosing whether to apply blockchain technology to improve the demand for traceable products.